Pozycja i znaczenie partii wywodzących się z systemu niedemokratycznego na scenie partyjnej w Polsce, Czechach, Słowacji i na Węgrzech po 1989 r. - Patkowski, Krzysztof (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2011)
Political parties rooted in a non-democratic system have become a significant element of party systems in Poland, the Czech Republic and Hungary, where they have taken an active part in the transformation process. The paper assesses the significance of these types of groupings for the construction of a new democratic system by means of a comparison of four members of the Vysehrad Group. The ideological profiles of these parties and their position in the party arena are defined. Finally, an attempt is made to answer the question of how these groupings have adapted to the new democratic system, why some of them continue to play a crucial role in politics even today, while others are found somewhere on the outskirts of political life. The author’s interests focus on the successors of those groupings that held full power before 1989: the Democratic Left Alliance in Poland, the Communist Party of Bohemia and Moravia in the Czech Republic, the Party of the Democratic Left in Slovakia, and the Hungarian Socialist Party. The example of the Communist Party of Bohemia and Moravia is of particular interest here as this is the only party that has not fundamentally changed its ideological profile and continues in isolation from other Czech groupings. At the same time, for twenty years, this same party has come third in the national elections, and even second in the European elections.